Application of Morpho in Urban Design and Planning Practice: Addressing Historical Urban Areas - Ardicoglu, Ruya (Mdpi, 2025)
The relationship between urban morphology and urban design or planning practice is inherently complex and multifaceted. A key challenge stems from the limited relevance and applicability of morphological tools to the practical issues encountered in professional planning contexts. This study seeks to address this gap by investigating how morphological analysis can inform the development of future urban plans and projects, particularly in areas where a strong historical fabric is integrated with contemporary urban structures. The research applies the Morpho method to historical urban environments, examining multiple morphological parameters, including street typology, block dimensions, plot density, the ratio of building height to street width, building alignment, and land-use distribution. Furthermore, the study introduces a new analytical criterion, the density of historical buildings within each street block, to enhance the methodological comprehensiveness of the analysis. The study also integrates the physical analysis of urban form with socio-economic dimensions by incorporating ownership status and population density data, thereby extending the framework and generating significant insights. Four neighborhoods in Beyo & gbreve;lu, Istanbul, were selected as case studies to illustrate the application of this method. The results demonstrate that the Morpho analysis can serve as a robust foundation for developing planning and design codes, facilitating the harmonious integration of historical urban areas with modern urban fabrics. The study concludes by suggesting how morphological knowledge can be translated into planning action by proposing planning strategies, emphasizing their potential role in guiding sustainable urban development. Ultimately, this study has important outcomes for sustainable urban development by addressing the integration between historical and modern patterns within ongoing urban alterations, the sustainability of historical patterns, and their integration with modern fabric. These outcomes can be used in urban policies for sustainable urban development in historical areas.
Keywords: urban morphology; urban sustainability; planning practice; Morpho method; historical areas; urban design; Istanbul; design code; sustainable development; conservation